Juvenile Nasopharyngeal Angiofibromas: Clinico-Radiological Evaluation - Bharat Bhushan Sharma; Shweta Sharma; Shashi Sharma; Akriti Sharma; Mir Rizwan Aziz (Highlights on Medicine and Medical Science Vol. 18, 2021)
Background: Juvenile nasopharyngeal angiofibroma (JNA) is also known as bleeding fibroma since it is highly vascular tumour.. This is a benign tumour that is locally aggressive and bleeds in prepubescent and young adults. The tumour expands due to the potential space available in the nasopharyngeal area without much of the resistance JNA requires early and accurate diagnosis by cross sectional modalities with the background setting of clinical symptomatology. This will helpful in early management and can avoid various future complications. Case Presentation: We present two cases of JNAs where the role of contrast enhanced computed tomography (CECT) is highlighted. These two examples of adolescent nasopharyngeal angiofibromas (JNAs) were diagnosed at at differing stages with the help of CECT reformatted reconstructed 3D images.. Conclusion: We lay a high value on the clinico-radiological evaluation in concluding the diagnosis. The adequate pre-operative radiological staging is required for the surgical management